An Analysis of Grammar Error and Abridged Sentence Redundancy on Text Titled (Unveiling the Architecture of Traditional Islamic Boarding Schools in Eastern Indonesia) - Mufidah Azzahra (SERIBU SUNGAI: Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study analyzes grammatical errors and sentence redundancy in the text entitled “Unveiling the Architecture of Traditional Islamic Boarding Schools in Eastern Indonesia” and presents abridged and paraphrased versions of the text to improve linguistic accuracy and clarity. The study also examines grammatical features relevant to English as a Foreign Language (EFL) instruction in Islamic boarding schools (Pesantren), highlighting their implications for curriculum content. Employing a descriptive qualitative approach, the analysis was conducted through in-depth examination and tabulated classification of grammatical errors to identify recurring patterns and text characteristics. The findings are expected to support EFL teachers in Indonesian Islamic boarding schools by providing insights into common grammatical issues that are often overlooked in Pesantren Curricula and by offering pedagogical implications for improving grammar instruction.